2010
DOI: 10.1038/eye.2009.317
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two tensioning suture sizes for 360° viscocanalostomy (canaloplasty): a randomised controlled trial

Abstract: Purpose To compare the safety and efficacy of two polypropylene (Prolene) sutures for tensioning of the inner wall of Schlemm's canal (SC) in black African patients with primary open-angle glaucoma (POAG) undergoing canaloplasty. Methods In a prospective randomised trial of 90 patients, canaloplasty was performed with a flexible microcatheter (iTrack-250A) and sodium hyaluronidate 1.4% (Healon GV). After complete circumferential dilatation of the SC, a Prolene suture, either 6-0 Prolene (group 1) or 10-0 Prole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 31 publications
(43 reference statements)
0
23
1
1
Order By: Relevance
“…Specifically, a mean reduction of 4.8 mmHg (25.3 % decrease rate) was found at 6 months after surgery. This decrease rate is somewhat lower than those reported by other authors [2,[4][5][6][7][8][9][10]. Lewis et al (2011) [6] in their 3-year international multicentre prospective study compared glaucoma patients having canaloplasty and combined cataract-canaloplasty surgery.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Specifically, a mean reduction of 4.8 mmHg (25.3 % decrease rate) was found at 6 months after surgery. This decrease rate is somewhat lower than those reported by other authors [2,[4][5][6][7][8][9][10]. Lewis et al (2011) [6] in their 3-year international multicentre prospective study compared glaucoma patients having canaloplasty and combined cataract-canaloplasty surgery.…”
Section: Discussioncontrasting
confidence: 81%
“…Several authors have reported successful outcomes after canaloplasty in terms of IOP and anterior segment integrity [2,[4][5][6][7][8][9][10]. Peckar and Koerber published a new method of channalography in 2008 for evaluating the outcome achieved with canaloplasty [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is that hypotony is practically eliminated by the intrinsic resistance of the distal physiological outflow system including episcleral venous pressure. 21,23 In the current study, no cases displayed bleb-associated complications (blebitis, endophthalmitis), or other serious complications such as extreme hypotony and detachment of the ciliary body or choroid. The 360-degree ST also decreases the learning curve of viscocanalostomy and canaloplasty, because the same surgical steps are performed when creating the superficial and deep scleral flaps and exposing the trabeculodescemet membrane.…”
Section: Discussionmentioning
confidence: 93%
“…Persistent SC dilation is also used in glaucoma by tensioning a suture placed within the entire circumference of SC. 44 The effects of pressure-induced reversal have, in addition, been studied in the laboratory and shown to cause marked changes in SC structural relationships. 32 Devices currently being inserted into SC in the operating room to bypass the TM are thought to achieve their best effect when placed near CCO; at the same time, efforts are made to avoid damage to or occlusion of CCO.…”
Section: Discussionmentioning
confidence: 99%